Phylogeny of the order Phyllachorales (Ascomycota, Sordariomycetes): among and within order relationships based on five molecular loci - Mardones Hidalgo, Melissa (2017)
The order Phyllachorales (Pezizomycotina, Ascomycota) is a group of biotrophic, obligate plant parasitic fungi with a tropical distribution and high host specificity. Traditionally two families are recognised within this order: Phyllachoraceae and Phaeochoraceae, based mostly on morphological and host characteristics. Currently, the position of the order within the class Sordariomycetes is inconclusive, as well as the monophyly of the order, and its internal phylogenetic structure. Here we present a phylogeny of the order Phyllachorales based on sequence data of 29 species with a broad host range resulting from a wide geographical sampling. We inferred Maximum Likelihood and Bayesian phylogenies from data of five DNA regions: nrLSU rDNA, nrSSU rDNA, ITS rDNA, and the protein coding genes RPB2, and TEF1. We found that the order Phyllachorales is monophyletic and related to members of the subclass Sordariomycetidae within Sordariomycetes. Within the order, members of the family Phaeochoraceae form a monophyletic group, and the family Phyllachoraceae is split into two lineages. Maximum Likelihood ancestral state reconstructions indicate that the ancestor of Phyllachorales had a monocotyledonous host plant, immersed perithecia, and a black stroma. Alternative states of these characters evolved multiple times independently within the order. Based on our results we redefine the family Phyllachoraceae and propose the new family Telimenaceae with Telimena erythrinae as type species, resulting in three families in the order. Species of Telimena spp. occur in several monocotyledonous and eudicotyledonous host plants except Poaceae, and generally have enlarged black pseudostroma around the perithecia, a character not present in species of Phyllachoraceae.